Estrategias didácticas y pensamiento crítico en estudiantes de nivel secundaria de la Institución Educativa N° 60276 Eugenio Rivera López distrito de Yavarí, Mariscal Ramón Castilla 2025 - Garcia Alejo, Romer (2025)
The purpose of this research was to determine the relationship between didactic strategies and critical thinking in secondary school students of the Educational Institution N° 60276 Eugenio Rivera Lopez district of Yavarí, Mariscal Ramón Castilla 2025. The study was applied and of non-experimental design. The sample was taken from the total population of 100 students. The findings show that 50.0% stated that the teaching strategies variable was good; likewise, 47.0% stated that the critical thinking variable was good. In addition, Spearman's Rho test showed a significance level of 0.000, which is less than 0.05, therefore, the null hypothesis was rejected and the alternative hypothesis is accepted; that is, there is a significant relationship between didactic strategies and critical thinking in secondary school students of the Educational Institution N° 60276 Eugenio Rivera Lopez district of Yavarí, Mariscal Ramón Castilla 2025.